Estimating the healthcare burden of Prurigo Nodularis in England: a CPRD database study - Donia Bahloul; Richard Hudson; Orsolya Balogh; Elgan Mathias; Ben Heywood; Ellen Hubbuck; Jules Tavi; Onyi Diribe; Robert McDonald; Simmi Wiggins; Anthony P. Bewley (Taylor & Francis Group, 2024)
Purpose: Prurigo nodularis (PN) is a skin disease characterized by intensely itchy skin nodules and is associated with a significant healthcare resource utilization (HCRU). This study aimed to estimate the HCRU of patients in England with PN overall and moderate-to-severe PN (MSPN) in particular.Methods: This retrospective cohort study used data from the Clinical Practice Research Datalink and Hospital Episode Statistics in England. Patients with Mild PN (MiPN) were matched to patients with MSPN by age and gender for the primary analysis. Patients were enrolled in the study between 1st April 2007 and 1st March 2019. All-cause HCRU was calculated, including primary and secondary care contacts and costs (cost-year 2022).Results: Of 23,522 identified patients, 8,933 met the inclusion criteria, with a primary matched cohort of 2,479 PN patients. During follow up, the matched cohort's primary care visits were 21.27 per patient year (PPY) for MSPN group and 11.35 PPY for MiPN group. Any outpatient visits were 10.72 PPY and 4.87 PPY in MSPN and MiPN groups, respectively. Outpatient dermatology visits were 1.96 PPY and 1.14 PPY in MSPN and MiPN groups, respectively.Conclusion: PN, especially MSPN, has a high HCRU burden in England, highlighting the need for new and improved disease management treatments.